I copied down the solutions from my teacher for this question and i understand up to this point:

⇒ 0 = sin 6x - sin 2x

The next step it is:

⇒ 0 = 2cos ((6x+2x)/2) sin ((6x-2x)/2)

I don't understand how that the addition formulas were used to get to this step.

The solution i copied down is below:

cos x + cos 3x = sin x + sin 3x

⇒cos x - sin x = sin 3x - cos 3x

now, squaring on both sides,

(cos x - sin x)^2 = (sin 3x - cos 3x)^2

⇒(cos x)^2 – 2 sin x cos x + (sin x)^2 = (sin 3x)^2 - 2sin 3x cos 3x+ (cos 3x)^2

⇒ 1-2 sin x cos x = 1-2sin 3x cos 3x

⇒ -2 sin x cos x = -2sin 3x cos 3x

⇒ sin x cos x = sin 3x cos 3x

multiplying both sides by 2,

⇒ 2sin x cos x = 2sin 3x cos 3x

⇒ sin 2x = sin 2(3x)

⇒ sin 2x = sin 6x

⇒ 0 = sin 6x - sin 2x

⇒ 0 = 2cos ((6x+2x)/2) sin ((6x-2x)/2)

⇒ 0 = 2cos 4x sin 2x

⇒ 0 = cos 4x sin 2x

case 1:

⇒ cos 4x = 0

⇒ cos 4x = cos π/2

⇒ 4x = 2nπ + π/2

⇒ x = nπ/2 + π/8

case 2:

⇒ sin 2x = 0

⇒ sin 2x = sin π

⇒ 2x = nπ + ((-1)^n)(π)

⇒ x = nπ/2 + ((-1)^n)(π)/2

⇒ x = [nπ/2 + π/8] or [nπ/2 + ((-1)^n)(π)/2]